A comparative analysis of four internationally traded farmed seafood commodities in China: domestic and international markets as key drivers. (10th September 2015) - Zhang, Wenbo; Murray, Francis J.; Liu, Liping; Little, David C.
Abstract: The historical development, current status and development trends of four internationally traded farmed seafood commodities, tilapia, penaeid shrimp, macrobrachium prawns and catfish in China were reviewed. China is the world's largest producer of tilapia, penaeid shrimp and macrobrachium prawns but, although farming of channel catfish and some indigenous catfish species is well developed, striped catfish failed to become established. In terms of global exports, China ranks first for tilapia and third for shrimp, while macrobrachium prawns and catfish mainly support domestic markets. Endogenous, biological characteristics and market demand explain the different courses of development and the differentiated focus on domestic and international trade. Tilapia and whiteleg shrimp production illustrated rapid growth in both domestic and international markets based on their favourable culture characteristics and well‐developed management systems. Huge production scale and domestic competition have resulted in China attaining a dominant and highly competitive position in the global tilapia market. High value of live freshwater prawns in local markets (and poor processing yield) has limited interest in exports, and local demand is also shifting the emphasis of shrimp production towards domestic markets, and a decline in its international market led to stagnation of channel catfish. Poor tolerance of seasonally low temperatures has restricted tilapia production to south China and completely inhibited the development of striped catfish as a commercial species. Live fish preference and costs of long‐distance transportation have restricted domestic consumption of tilapia. A balance between domestic consumption and export is required to optimise future growth opportunities for the industry.